Association of sociodemographic and nutritional factors with risk of neural tube defects in the North Indian population: a case–control study. Issue 2 (23rd January 2013) - Deb, Roumi; Arora, Jyoti; Saraswathy, Kallur N; Kalla, Aloke K
Abstract: Objective: To assess the role of sociodemographic and nutritional factors in the incidence of births affected by neural tube defects (NTD) in the North Indian population. Design: Case–control study. Setting: Government hospitals of Delhi, India. Subjects: Subjects comprised 284 mothers of NTD children (cases) and 568 mothers of healthy children (controls). Results: Significant differences were found between case and control mothers with respect to maternal age ( P = 0·005), type of drinking water ( P = 0·03) and consumption of milk ( P = 0·01). Univariate and multivariate analysis suggested an association of unpasteurized milk use, low consumption of vegetables, low consumption of fruits and vegetarian dietary habits with NTD births. Further, variation in the risk factors for upper and lower NTD types was also observed, pointing towards phenotypic heterogeneity in the aetiology. Conclusions: The results of the present study suggest an increased risk of NTD infants in mothers with low consumption of vegetables, fruits and milk and having vegetarian dietary habits. So, in order to reduce these devastating birth defects in future offspring, better nutritional care should be provided to mothers by suggesting dietary modifications and augmenting additional micronutrient supplementation during the periconceptional period.